P957Characteristics of atrial tachycardia after mitral surgey via biatrial trans-septal approach using high density mapping system. (18th June 2020) - Cataldi, C; Andronache, M; Eschalier, R; Jean, F; Bosle, R; Farhat, M; Massoullie, G
Abstract: Background The biatrial trans-septal approach (BTSa) ameliorates mitral valve (MV) exposure in difficult cases when routine left atriotomy doesnt"t allow it. Main steps are an oblique incision on the right atrium (RA), reaching medially the right pulmonary veins (PV), a septal incision from the fossa ovalis, extended up to reach the first incision, then on the left atrium (LA). Purpose: We aim to study the arrhythmic burden in this post-surgical context, focusing on atrial tachycardia (AT), to investigate the complexity of several possible circuits. Methods All patients (>18yo) with previous MV surgery via BTSa for MV repair or replacement, who underwent ablation of AT from January 2017 to September 2019, were enrolled. Patients ablated for persistent or paroxysmal AF, or with AF during the index procedure were excluded. Patients with associated surgery on other valves or congenital defects, coronary, surgical or percutaneous rhythm interventions weren't excluded. Electroanatomical mapping was created using 2 different high-density mapping system. Substrate and activation map and radio-frequency (RF) ablation (25-50W, Ablation Index target 400) were realized. Cartographies were analysed to evaluate AT re-entry circuit, critical isthmus (CI) location and characterization, atrial vulnerability. Procedural outcomes (AT termination, sinus rhythm (SR) restoration, anti-arrhythmic drugs (AAD) withdrawal), and peri-procedural complications were also evaluated. Results We enrolled 49 patients (median age 57 ± 15), finding a maximum of 5 AT per procedure (2 ± 1). A total of 112 AT were mapped: the majority (72%) were persistent AT, 8, 2% common atrial flutter. Cycle length was 314 ± 74 msec, with proximal-distal activation of coronary sinus (78%). A multiple re-entry circuit was observed in 70% of index AT. We identified 152 critical isthmus (maximum 5 per procedure). Only 27, 9% of our patients had a single CI; CTI was the most frequent one (n = 37), envolved in 33% of all AT, while BTS scars altogether were envolved in 65% AT. A complete AT circuit was mapped in the RA, the LA and both atria in respectively 49%, 11, 5% and 39%AT. The distribution of CIs is shown in figure 1. Biatrial and left AT leads to superior procedure, RF and fluoroscopy duration (p <0, 05). SR was restored in 93, 4%of patients, requiring a DC shock in 4 cases. Immediate AAD withdrawal was achieved after 41%procedures. No pericardial, oesophageal, vascular or phrenic complication occurred. 4 pace-maker implantations were realized because of 3 interatrial, 2 AV block and a sinus node dysfunction. Conclusions AT occurring after a BTSa have a high prevalence of multiple re-entry circuits with multiple critical isthmus. Ablation in this context is feasible and safe but often requires a left atrial access. Mapping of both atria should be considered to identify critical isthmus and tailored ablation strategy.